Biology of Gratiana boliviana, the First Biocontrol Agent Released to Control Tropical Soda Apple in the USA - Julio C. Medal; D. Gandolfo; William Overholt; Philip Stansly; Amy Roda; Lance Osborne; Kenneth Hibbard; R. Gaskalla; E. Burns; J. Chong; Brent Sellers; S. Hight; et al. (EDIS, 2007)
Revised! ENY-826, a 3-page illustrated fact sheet by J. C. Medal, D. Gandolfo, W. Overholt, P. Stansly, A Roda, L. Osborne, K. Hibbard, R. Gaskalla, E. Burns, J. Chong, B. Sellers, S. Hight, and J. P. Cuda, describes the TSA tortoise beetle, which was released in Florida in 2003 and has been established for the control of Tropical Soda Apple in the USA. Includes references. Published by the UF Department of Entomology and Nematology, August 2007.